EFFECTS OF LYCOPENE SUPPLEMENTATION ON GROWTH, BLOOD PROFILE, AND MINERAL DIGESTIBILITY IN Cirrhinus mrigala FED CANOLA MEAL-BASED DIETS - Tahreem Abbas; Muhammad Zubair-ul-Hassan Arsalan; Syed Makhdoom Hussain; Muhammad Asrar; A. Riaz; Shafaqat Ali; Rukhsanda Aziz; Faiza Afzal; Muhammad Amjad; Zainab Akram (Journal of Animal and Plant Sciences, 2026)
<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; line-height: 149%; font-family: 'Times New Roman',serif; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: 1.0pt; mso-ligatures: standardcontextual; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Lycopene is a lipophilic natural antioxidant that effectively neutralizes oxygen and free radicals. The present study was conducted to investigate the effects of lycopene supplemented canola meal-based diets on growth, nutrient digestibility, hematology, carcass composition, and mineral digestibility of Cirrhinus mrigala fingerlings. Six concentrations of lycopene supplementation (0%, 1%, 2%, 3%, 4%, and 5%) were prepared. A feeding rate of 5% live body weight was given to the fish for three months, stocked in tanks (n=270; average weight= 5.31 ± 0.039 g). The results showed that weight gain % (288.49±9.82%), FCR (1.332±0.03), protein content (77.50±0.87%), and gross energy (75.42±0.94%) were significantly higher in the group fed 3% lycopene supplemented diets, <span style="font-size: 10.0pt; mso-bidi-font-size: 11.0pt; line-height: 149%; font-family: 'Times New Roman',serif; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: 1.0pt; mso-ligatures: standardcontextual; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">while crude fat digestibility (77.94±1.43%) was maximum at 2% lycopene level. <span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; line-height: 149%; font-family: 'Times New Roman',serif; mso-fareast-font-family: 'Times New Roman'; mso-font-kerning: 1.0pt; mso-ligatures: standardcontextual; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Furthermore, the hematological parameters were significantly improved at Test-diet IV (3% lycopene supplementation). Moreover, the body composition parameters and mineral digestibility (Ca, K, Fe, Cu, Zn, Na, and P) were substantially enhanced when C. mrigala were fed the Test-diet IV.  In conclusion, the supplementation of 3% lycopene in canola meal-based diets is recommended for C. mrigala fingerlings, enhancing growth performance, nutritional digestibility, and blood parameters.
Keywords: Lycopene; aquaculture; fishmeal; canola meal; supplementation